Analysis of hotel visits in Ambon city using the naive bayes algorithm - Henderina Doren; Jermias Victor Manuhutu; Yoakhina Nicole Makaruku; Wilma Latuny; Apritiwi Maimina (Institute of Computer Science (IOCS), 2026)
The rapid growth of tourism in Ambon City has increased competition among accommodations, necessitating data-driven performance evaluations. Prospective tourists often struggle with unstructured online reviews, while hotel management requires precise insights for improvement. This study aims to systematically classify hotel performance in Ambon City using the Naïve Bayes Algorithm based on reviews from platforms like Agoda and TripAdvisor. Adopting a descriptive quantitative methodology, the study processes and labels performance data as